Enterococcus faecalis Adapts to Antimicrobial Conjugated Oligoelectrolytes by Lipid Rearrangement and Differential Expression of Membrane Stress Response Genes - Chilambi, Gayatri Shankar; Hinks, Jamie; Matysik, Artur; Zhu, Xinyi; Choo, Pei Yi; Liu, Xianghui; Chan-Park, Mary B.; Bazan, Guillermo C.; Kline, Kimberly A.; Rice, Scott A. (Frontiers in Microbiology, 2020)
Conjugated oligoelectrolytes (COEs) are emerging antimicrobials with broad spectrum activity against Gram positive and Gram negative bacteria as well as fungi. Our previous in vitro evolution studies using Enterococcus faecalis grown in the presence of two related COEs (COE1-3C and COE1-3Py) led to the emergence of mutants (changes in liaF and liaR) with a moderate 4 to16 fold increased resistance to COEs. The contribution of liaF and liaR mutations to COE resistance was confirmed by complementation of the mutants, which restored sensitivity to COEs. To better understand the cellular target of COEs, and the mechanism of resistance to COEs, transcriptional changes associated with resistance in the evolved mutants were investigated in this study. The differentially transcribed genes encoded membrane transporters, in addition to proteins associated with cell envelope synthesis and stress responses. Genes encoding membrane transport proteins from the ATP binding cassette superfamily were the most significantly induced or repressed in COE tolerant mutants compared to the wild type when exposed to COEs. Additionally, differences in the membrane localization of a lipophilic dye in E. faecalis exposed to COEs suggested that resistance was associated with lipid rearrangement in the cell membrane. The membrane adaptation to COEs in EFC3C and EFC3Py resulted in an improved tolerance to bile salt and sodium chloride stress. Overall, this study showed that bacterial cell membranes are the primary target of COEs and that E. faecalis adapts to membrane interacting COE molecules by both lipid rearrangement and changes in membrane transporter activity. The level of resistance to COEs suggests that E. faecalis does not have a specific response pathway to elicit resistance against these molecules and this is supported by the rather broad and diverse suite of genes that are induced upon COE exposure as well as cross-resistance to membrane perturbing stressors.